Agrobacterium tumefaciens–mediated genome editing in banana - Tripathi, J.; Tripathi, L. (Humana Press, 2025)
This protocol outlines the Agrobacterium tumefaciens–mediated transformation process for genome editing in banana (Musa spp.). As a crop of significant agricultural and economic importance globally, improving banana cultivars is crucial for addressing challenges such as disease resistance, climate resilience and yield enhancement. The procedure presented here involves the establishment of embryogenic cell suspensions (ECSs) from immature male flowers, followed by co-cultivation with Agrobacterium containing the desired gene construct. Key steps include callus induction, ECS generation and maintenance, transformation using plasmid construct containing genome editing reagents such as CRISPR/Cas9, and regeneration. The method ensures the editing of target genes in the banana genome, facilitating genetic improvements.